Optical radiation special features from plasma of low pressure discharge initiated by microwave radiation with stochastic jumping phase - Karas, V.I.; Alisov, А.F.; Bolotov, О.V.; Golota, V.I.; Karas, I.V.; Yegorov, А.М.; Zagorodny, A.G.; Zagrebelny, I.А.; Potapenko, I.F. (Вопросы атомной науки и техники, 2013)
We study the plasma discharge, initiated by microwave radiation with stochastically jumping phase (MWRSJP) in a coaxial waveguide at the optimal mode of the beam-plasma generator. Present results continue the line of the previous research. In this paper we experimentally examine the optical characteristics of the discharge plasma in a wide range of both an air pressure and microwave radiation power. In general the research aims to develop a new type of sources of optical radiation. Вивчаєтся плазма розряду, ініційованого мікрохвильовим випромінюванням, зі стохастично стрибковою фазою в коаксиальному хвилеводі в оптимальному режимі пучково-плазмового генератора. Наведені результати є продовженням раніше проведених досліджень. Експериментально досліджувались оптичні характеристики розрядної плазми в широкій області тисків повітря та потужності мікрохвильового випромінювання. Метою дослідження є розвиток нового типу джерела оптичного випромінювання. Изучается плазма разряда, инициируемого микроволновым излучением, со стохастически прыгающей фазой в коаксиальном волноводе в оптимальном режиме пучково-плазменного генератора. Представленные результаты являются продолжением ранее проведенных исследований. Экспериментально исследовались оптические характеристики разрядной плазмы в широкой области давлений воздуха и мощности микроволнового излучения. Цель исследования – развитие нового типа источника оптического излучения.